2015
DOI: 10.1182/blood-2014-11-607317
|View full text |Cite
|
Sign up to set email alerts
|

Adverse maternal and perinatal outcomes in pregnant women with sickle cell disease: systematic review and meta-analysis

Abstract: Key Points• Pregnant women with sickle cell disease have high risks of adverse maternal and perinatal outcomes.• The risks are greatest for those with HbSS disease (vs HbSC disease) and those in low income (vs high income) countries.A systematic review and meta-analysis of observational studies were conducted to quantify the association between sickle cell disease in pregnancy and adverse maternal and perinatal outcomes. 32-5.98). Meta-regression demonstrated that genotype (HbSS vs HbSC), low gross national i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
232
4
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(256 citation statements)
references
References 43 publications
11
232
4
9
Order By: Relevance
“…Adolescents and adults with SCD may experience a wide array of reproductive issues including delayed puberty, hypogonadism, infertility, and pregnancy complications [118][119][120][121]. In men with SCD, vaso-occlusion and recurrent testicular infarction may contribute to hypogonadism [122,123].…”
Section: Reproductive Health In Adults With Scdmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescents and adults with SCD may experience a wide array of reproductive issues including delayed puberty, hypogonadism, infertility, and pregnancy complications [118][119][120][121]. In men with SCD, vaso-occlusion and recurrent testicular infarction may contribute to hypogonadism [122,123].…”
Section: Reproductive Health In Adults With Scdmentioning
confidence: 99%
“…Less is known about fertility and reproductive health in women with SCD, and few studies have addressed this prospectively [129,130] [121]. Another meta-analysis reported a benefit of prophylactic blood transfusions in reducing maternal mortality, preterm births, and neonatal deaths [131]; however, this needs to be evaluated prospectively in a randomized trial.…”
Section: Reproductive Health In Adults With Scdmentioning
confidence: 99%
“…Pregnancy in women with SCD is currently viewed more favorably 4 than it was during the 1970s, when its avoidance was recommended. 5 Nevertheless, maternal and fetal morbidity and mortality [6][7][8][9] are still encountered, and further examination of interventions capable of mitigating these adverse pregnancy outcomes is needed.…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review of maternal and perinatal outcomes of pregnant women with sickle cell disease it was concluded that the risks are higher for pregnant women with sickle cell anemia -HbSS, and in low-income countries they are more susceptible to morbidity and mortality, in which access antenatal care with specialized multidisciplinary team are not properly systemized and implemented [23].…”
Section: Discussionmentioning
confidence: 99%